The Influence of Price and Taste Perception on Consumer Decisions to Use the Grab Food Application on Jalan Perisai Rantauprapat - Muhammad Alwi Ritonga; Midrawati Hasibuan; Nurhabibah Ritonga (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to analyze the influence of price perception and taste on consumer decisions in using the Grab Food application on Jalan Perisai Rantauprapat. The method used is a quantitative approach with a survey technique, where data is collected through questionnaires distributed to consumers who use the Grab Food service. Data analysis was carried out using multiple linear regression to identify the relationship between independent variables (price perception and taste) with the dependent variable (consumer decision). The results of the study indicate that price perception and taste have a significant positive influence on consumer decisions in choosing the Grab Food service, with the results of t count> t table The results of the simultaneous test show that the significance value for the influence of Price Perception (X1) and Taste (X2) on Consumer Decisions (Y) is 0.000 <0.05 with an F count value of 17.253> F table 3.19 so that there is a simultaneous influence between X1 and X2 on Y in Rantauprapat. Keywords: Price perception, taste, consumer decision, Grab Food, Rantauprapat. This research is expected to provide insight for Grab Food business actors and service providers in improving the quality of service and consumer experience.